Disease burden and patient needs and benefits in anogenital psoriasis: developmental specificities for person‐centred healthcare of emerging adults and adults. (29th January 2020) - da Silva, N.; von Stülpnagel, C.; Langenbruch, A.; Danckworth, A.; Augustin, M.; Sommer, R.
Abstract: Background: Establishing romantic relationships involving cohabitation and/or sexual intercourse is an overriding task for many people during emerging adulthood, i.e. from their late teens through the twenties. The diagnosis of anogenital psoriasis may hinder social/intimate relationships, resulting in higher disease burden in this age group. Objectives: To compare the disease burden and patient needs/benefits between emerging adults (18–30 years) and adults (>30 years) with psoriasis, with and without anogenital involvement; and to identify sociodemographic/clinical variables accounting for better patient‐reported outcomes. Methods: Patients aged ≥18 years with psoriasis vulgaris were recruited within a cross‐sectional nationwide survey randomly assigning 157 dermatology practices/clinics in Germany. Anogenital involvement was established based on a high‐resolution grid on the topology of psoriasis. The main outcome measures were the Psoriasis Area and Severity Index (PASI), the EuroQoL visual analogue scale (EQ‐VAS), the Dermatology Life Quality Index (DLQI) and the Patient Benefit Index (PBI). Results: Participants were 1921 patients: 173 emerging adults and 1749 adults >30 years. Anogenital involvement was observed in 621 patients (32.3%). Patient with anogenital psoriasis reported decreased health and more QoL impairments compared with those without anogenital lesions. Emerging adults presented more QoL impairments and less treatment benefits than older patients, and they were more prone to underrate a wide range of needs, except when the anogenital area was affected. Beyond anogenital involvement and higher disease severity, less treatment benefits were associated with more QoL impairments, particularly for emerging adults. Conclusions: The developmental instability of many emerging adults may result in difficulties to establish/adhere to treatment goals and thus in decreased perception of treatment benefit and more QoL impairments. Anogenital involvement is a risk factor for increased disease burden regardless of age. Assessing anogenital involvement in all patients and helping younger patients to define/adhere to treatment goals should be prioritized in patient‐centred healthcare for psoriasis.